A prospective multicentre surveillance study to investigate the risk associated with contaminated sinks in the intensive care unit. (September 2021) - Valentin, Anne-Sophie; Santos, Sandra Dos; Goube, Florent; Gimenes, Rémi; Decalonne, Marie; Mereghetti, Laurent; Daniau, Côme; van der Mee-Marquet, Nathalie; ,; Abdoush, H.; Alfandari, S.; Allaire, A.; et al.
Abstract: Objectives: The aim was to assess the incidence of sink contamination by multidrug-resistant (MDR) Pseudomonas aeruginosa and Enterobacteriaceae, risk factors for sink contamination and splashing, and their association with clinical infections in the intensive care setting. Methods: A prospective French multicentre study (1 January to 30 May 2020) including in each intensive care unit (ICU) a point-prevalence study of sink contamination, a questionnaire of risk factors for sink contamination (sink use, disinfection procedure) and splashing (visible plashes, distance and barrier between sink and bed), and a 3-month prospective infection survey. Results: Seventy-three ICUs participated in the study. In total, 50.9% (606/1191) of the sinks were contaminated by MDR bacteria: 41.0% (110/268) of the sinks used only for handwashing, 55.3% (510/923) of those used for waste disposal, 23.0% (62/269) of sinks daily bleached, 59.1% (126/213) of those daily exposed to quaternary ammonium compounds (QACs) and 62.0% (285/460) of those untreated; 459 sinks (38.5%) showed visible splashes and 30.5% (363/1191) were close to the bed (<2 m) with no barrier around the sink. MDR-associated bloodstream infection incidence rates ≥0.70/1000 patient days were associated with ICUs meeting three or four of these conditions, i.e. a sink contamination rate ≥51%, prevalence of sinks with visible splashes ≥14%, prevalence of sinks close to the patient's bed ≥21% and no daily bleach disinfection (6/30 (20.0%) of the ICUs with none, one or two factors vs. 14/28 (50.0%) of the ICUs with three or four factors; p 0.016). Discussion: Our data showed frequent and multifactorial infectious risks associated with contaminated sinks in ICUs.